الأهمية الاقتصادية للمواد الناتجة عن تجوية الصخور البركانية-الرسوبية في الجزء الأوسط من الساحل السوري (Latakia University Journal -Basic Sciences Series, 2016)
تكمن أهمية البحث في الطلب المتزايد بشكل كبير على مواد البناء، وخصوصاً منها الداخلة في صناعة الإسمنت وغيرها. فقد توجه الاهتمام إلى إيجاد مواقع بديلة للخامات الأولية إضافة إلى عملية إحياء، وإعادة تأهيل للمقالع القديمة, إذ إن الاستجرار المقلعي الجائر لهذه المواد سيؤدي في النهاية إلى هدرها، ونفادها قبل الإستفادة منها بالشكل الاقتصادي الأمثل، حيث تم تحديد مواقع الأمل في رقعتي بانياس وطرطوس. ونستطيع القول إن تجوية المنتجات البركانية في منطقة الدراسة وفسادها جاء نتيجة مباشرة للظروف المناخية التي كانت سائدة (عمليات التجوية والفساد والتعرية الفيزيائية والكيميائية من رطوبة ورياح، وأمطار، ودرجة حرارة وجريان المياه السطحية)، وقد أدى التكتونيك الذي أصاب هذه التشكيلات لاحقاً إلى رفع درجة التجوية، والتعرية، وجعلها أكثر فعالية لإنتاج بعض الأكاسيد, مثل: (أكسيد الكالسيوم، وأكسيد الحديد، وأكسيد الألمنيوم، وفساد مكونات الصخر، وتركيز الغضاريات), وذلك على شكل مستويات من الفساد الغضاري، وفقاً للتحاليل الجيوكيميائية المنفذة في هذا البحث . The importance of this scientific research stems from the increasing demand for building materials, especially the materials involved in concrete industry. The attention was directed towards finding alternative locations for primary oresin addition to the process of reconstructing old mines as the continues inequitable taking of these materials will eventually result in wasting those resources losing them before using them in an economical suitable way. We have defined the hope positions in the areas of Banias and Tartous. We can say that deterioration of volcanic products in those areaswas a direct result of suitable climatic circumstances which were predominant (weathering process, deterioration, physical erosion, and chemical like wetness, wind, rain, temperature, and surface water streaming). The tectonic which attacked those formations later served to boost the weathering and erosion degree so that it became more effective for the production of some oxides such as (calcium oxide, iron oxide, aluminum oxide, deterioration of rock components, and concentration of clay) asplain strataof clay deterioration according to geochemical analyses conducted in this research.